Revealing Carbon Patterns Across Mangrove Density Variations Using Sentinel-2 NDVI - Nasir, Anugrahandini; Herawaty, Herawaty; Ismail, Ismail; Syah, Muh Izzul Muslimin (Jurnal Wasian, 2025)
Mangrove ecosystems play a crucial role in maintaining the balance of coastal ecosystems and mitigating climate change due to their ability to absorb and store carbon. This study aims to estimate carbon stocks across different mangrove density levels on Bangko-bangkoang Island, Pangkep Regency, South Sulawesi Province. The methods employed include Sentinel-2 imagery analysis using the Google Earth Engine platform to identify vegetation density based on the Normalized Difference Vegetation Index (NDVI) and estimate carbon stocks using an allometric model and field data. The Sentinel-2 image analysis revealed that the mangrove vegetation cover on Bangko-bangkoang Island spans 16.04 ha. NDVI results show that mangroves in the low-density class cover 8.97 ha (56%), the medium-density class covers 3.71 ha (23%), and the high-density class covers 3.34 ha (21%). Field surveys confirmed the presence of three mangrove species on the island: Rhizophora mucronata, Rhizophora stylosa, and Sonneratia alba. Regression analysis conducted to assess the relationship between NDVI values and carbon stocks revealed the best model as an exponential function with the equation y = 0.0043e(11.726x), yielding a coefficient of determination (R²) of 0.683. The average carbon stock for the low-density class is 22.35 tons C/ha, for medium density is 67.1 tons C/ha, and for high density is 111.85 tons C/ha. These findings emphasize the important role of mangroves in climate change mitigation and provide scientific evidence for mangrove conservation efforts, particularly in enhancing vegetation density to optimize carbon storage.